Great Canadian Lagerstätten 3. Late Ordovician Konservat-Lagerstätten in Manitoba - Young, Graham A.; Rudkin, David M.; Dobrzanski, Edward P.; Robson, Sean P.; Cuggy, Michael B.; Demski, Matthew W.; Thompson, Deborah P. (Geoscience Canada, 2013)
Konservat-Lagerstätten, deposits in which soft-bodied or lightly sclerotized fossils are preserved, are very rare in Ordovician strata. Three significant sites are known from Upper Ordovician rocks in Manitoba: at Cat Head – McBeth Point, William Lake, and Airport Cove. These sites are in two distinct sedimentary basins: the former two are in the Williston Basin, while the latter is in the Hudson Bay Basin. All three sites contain marine fossils, but each has a different assemblage that contributes a distinct piece of the diversity picture. Important groups represented at one or more of the sites include seaweeds (algae), sponges, cnidarian medusae (jellyfish), conulariids, trilobites, eurypterids, xiphosurids (horseshoe crabs), and pycnogonids (‘sea spiders’). The different biotas reflect depositional conditions at each site. Many of the fossils are unknown elsewhere in the Ordovician at the family level or higher. The province of Manitoba therefore makes a significant contribution to knowledge of Late Ordovician biodiversity. SOMMAIRE Les lagerstätten de conservation, ces sédiments contenant des fossiles d’organismes à corps mou ou légèrement sclérotisés particulièrement bien conservés, sont très rares dans les strates ordoviciennes. Trois sites d’importance sont connus dans des roches de l'Ordovicien supérieur à Cat Head, Manitoba, soit McBeth Point, William Lake et Airport Cove. Ces sites sont situés dans deux bassins sédimentaires distincts : les deux premiers sont situés dans le bassin de Williston, tandis que le second est situé dans le bassin de la baie d'Hudson. Les trois sites contiennent des fossiles marins, mais chacun présente un assemblage différent, chacun montrant une composante distincte de la diversité biologique d’alors. Les groupes les plus importants représentés, dans un ou plusieurs de ces sites, sont les algues, les éponges, les cnidarian medusae (méduses), les conularides, les trilobites, les euryptérides, xiphosurides (limules) et pycnogonides. Les différents biotopes reflètent les conditions de dépôt de chaque site. Nombre de ces fossiles sont inconnus ailleurs dans l'Ordovicien, au niveau de la famille ou du taxon supérieur de la classification. Ainsi, la province du Manitoba offre-t-elle une contribution importante à la connaissance de la biodiversité de l'Ordovicien supérieur.